Cordillera in June essays celebrating June Prill-Brett, anthropologist - Tapang, Bienvenido P. (University of the Philippines Press, 2007)
"This book of essays, Cordillera in June, is dedicated to June Prill-Brett, anthropologist. Every paper in the collection resonates with a theme that she has worked on as a scholar of the Cordillera. In her season of grace, we at UP Baguio celebrate June through this collection of articles contributed by her peers, colleagues, and one of her former students."--Preface.